Fluorine and chlorine substituted adamantyl-urea as molecular tools for inhibition of human soluble epoxide hydrolase with picomolar efficacy - Vladimir V. Burmistrov; Christophe Morisseau; Dmitry V. Danilov; Boris P. Gladkikh; Vladimir S. D’yachenko; Nikolay A. Zefirov; Olga N. Zefirova; Gennady M. Butov; Bruce D. Hammock (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
Series of 1,3-disubstituted ureas and diadamantyl disubstituted diureas with fluorinated and chlorinated adamantane residues were shown to inhibit human soluble epoxide hydrolase (sEH) with inhibition potency ranging from 40 pM to 9.2 nM. The measured IC50 values for some molecules were below the accuracy limit of the existing in vitro assays. Such an increase in activity was achieved by minimal structural modifications to the molecules of known inhibitors, including 4-[trans-4-(1-adamantylcarbamoylamino)cyclohexyl]oxybenzoic acid. For the chlorinated homologue of the latter the sharp jump in inhibitory activity can be (according to molecular dynamics data) the result of interactions – Cl-π interaction. Considering the extremely high inhibitory activity, acceptable solubility and partial blockage of metabolically sensitive centres in their structures, some compounds are of interest for further in vivo biotesting.